Improving Elementary School Students' Mathematical Literacy and Character through Ethnomathematics and Deep Learning in the Era of the Industrial Revolution 4.0 - Santy Widiani (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2026)
Technological developments in the Industrial Revolution 4.0 era demand learning innovations that focus not only on knowledge but also on character building and digital literacy. This study aims to develop and test the effectiveness of an integrative learning model based on ethno-mathematics and deep learning to improve the mathematical literacy and character of elementary school students. A mixed methods quasi-experimental design was used in two classrooms in Bandung City, using a mathematical literacy test, character observation, and interviews as instruments. The results showed a significant increase in mathematical literacy in the experimental class compared to the control class (p < 0.05) with an effect size of 1.12. Qualitative findings indicated that students were better able to relate mathematical concepts to local cultural contexts. In conclusion, this integrative learning model effectively strengthens conceptual understanding, personalized learning, and student character, and provides theoretical and practical contributions to the development of culture- and technology-based mathematics learning in line with 21st-century demands.